Beyond urban ecomodernism: How can degrowth-aligned spatial practices enhance urban sustainability transformations. (May 2023) - De Castro Mazarro, Alejandro; George Kaliaden, Ritu; Wende, Wolfgang; Egermann, Markus
For spatial practices such as architecture, urban design and planning, degrowth remains an abstract concept, as there is no clear alignment of its principles into spatial strategies. To bridge this gap, this paper examines how degrowth can be operationalised into sustainable spatial practices. Through a review of more than 200 sustainable spatial projects across the world operating at the building, neighbourhood and citywide scales, the paper shows that while the majority of sustainable interventions representative of dominant architecture and urban design culture do not align to degrowth principles, a significant number of examples using sustainability strategies such as convivial technologies, building retrofitting, urban renaturation and revitalisation, eco-urbanisation and spatial infrastructure upgrading are in fact aligned to degrowth principles. We suggest that these examples form a potential stepping-stone to enable an urban design and building culture rooted in a degrowth agenda, however further research and conceptualisation are needed to enable this to happen.